Negative childbirth experience in relation to mode of birth and events during labour: A mixed methods study. (March 2023) - Viirman, Frida; Hess Engström, Andrea; Sjömark, Josefin; Hesselman, Susanne; Sundström Poromaa, Inger; Ljungman, Lisa; Skoog Svanberg, Agneta; Wikman, Anna
Highlights: Negative childbirth experience is a multifaceted concept. Fear-based emotions appear to dominate negative childbirth experience. The nature of negative birth experience was unrelated to mode of birth and events during labour. Abstract: Objective: To explore descriptions of negative childbirth experience in relation to mode of birth and events during labour. Design: A descriptive study using a convergent mixed methods design. Written responses to open-ended online questions regarding negative childbirth experience were explored using qualitative content analysis. Generated sub-themes were quantified, and stratified on mode of birth and events during labour. Participants and setting: 112 women with low ratings of overall childbirth experience, participating in a randomised controlled trial evaluating internet-based cognitive behavioural therapy in Sweden. Qualitative data were collected before randomisation, three months postpartum. Results: Four sub-themes emerged from the qualitative analysis: Experiencing fear-based emotions, Experiencing physical distress, Being affected by caregivers' and partner's behaviour and Being affected by bad facilities and poor organisation . Only small differences were found when stratifying sub-themes on mode of birth and events during labour. Regardless of mode of birth and events during labour, the childbirth experience was dominated by fear-based emotions. Key conclusions and implications for practice: Mixed-methods analyses demonstrate the challenges in understanding negative childbirth experience in relation to mode of birth and specific events during labour, with results clearly showing the multifaceted nature of this concept. The central role of fear in relation to negative childbirth experience should be considered when designing support during and after labour, to prevent adverse effects of the childbirth experience.